Lipoprotein SPD_1609 of Streptococcus pneumoniae Promotes Adherence and Invasion to Epithelial Cells Contributing to Bacterial Virulence - Yang, Xiao-Yan; Li, Nan; Xu, Jing-Yu; Sun, Xuesong; He, Qing-Yu (Frontiers in Microbiology, 2019)
In most bacteria, iron plays a vital role in pathogenesis processes. To support survival and infection, Streptococcus pneumoniae has evolved three ABC transporters, PiaABC, PiuABC, and PitABC. Moreover, indirect evidence supports that operon 804 may be a novel ABC transporter in S. pneumoniae. We have recently described the identification of lipoprotein SPD_1609 in operon 804; however, whether the SPD_1609 protein affects the virulence of S. pneumoniae has not yet been studied. In the present work, alignment analysis showed that lipoprotein SPD_1609 is conserved in a variety of gram-positive bacteria, and deletion of the spd_1609 gene led to a reduction in adherence and invasion of S. pneumoniae to host cells. RT-qPCR assays indicated that deletion of the spd_1609 gene resulted in decreased expression of genes involved in colonization. Furthermore, decreased virulence in a mouse bacteremia infection model caused by the loss of the lipoprotein encoded by spd_1609 was also demonstrated. Overall, these data provide insights into the functional role of lipoprotein SPD_1609 in pneumococcal pathogenesis, suggesting its possibility to be developed as a novel S. pneumoniae vaccine candidate.